TALES OF MOTHERS 2 : OF LOVE AND COURAGE - Raudah Mohd. Yunus, editor; Md. Mahmudul Hasan, editor (Seri Kembangan, Selangor : Iman Publication Sdn. Bhd., 2019)
Tales of Mothers: Of Love and Courage features 10 real-life anecdotes from mothers and their stories of unconditional love and bravery in the face of adversity. Theses stories will break hearts, but they will inspire within us a newfound respect and appreciation for our mothers.